ANALISIS KESALAHAN MAHASISWA MENENTUKAN PENYELESAIAN PERTIDAKSAMAAN NILAI MUTLAK DALAM MATA KULIAH KALKULUS - Saparwadi; Desventri Etmy (Jurnal Pemikiran dan Penelitian Pendidikan Matematika (JP3M), 2019)
The purpose of this study is to describe the aspects of mistakes made by semester 1 students of Bumigora University, Mataram, Departement of Computer Science in solving questions related to the material Absolute Inequality. The research method used is descriptive qualitative and quantitative descriptive methods. Based on the results of diagnostic tests conducted on 121 students, it is found that there are still many students who make mistakes in solving problems including students' concept errors on the material inequality absolute value of 47.1%, principle errors of 60.3%, and operating errors of 81, 5% Constraints experienced by students so that errors occur in working on problems related to inequality absolute values, namely: (a) Students are still unable to understand the intended purpose of the problem, (b) Students are not capable of simple mathematical operations such as addition, subtraction, fraction worth and others; (c) When sitting in school, students are only given simple examples in solving problems.